EKSISTENSI DAN AJARAN KELOMPOK PENGHAYAT KAWERUH JAWA DIPA DI TULUNGAGUNG - Mohamad Imron Rosadi (LP2M IAIN Tulungagung, 2015)
After the end of the New Order regime, various groups of penghayat showed back existence. In the reign of President Soeharto, this group had received discriminatory treatment, whether committed by state and fellow citizens of Indonesia. Discriminations that shaped the state rules and regulations of the moral insult other religions. With this discriminatory treatment, these groups then chose to move religious status, and some chose to hide the identity and activities. Kaweruh Jawa Dipa groups have been known to show the back of existence and activity. So that its presence in the community enough to invite attention. In this study, the object being studied is the existence and teaching of Kaweruh Jawa Dipa group in Tulungagung. This research is a field of research (qualitative). Sources were obtained based on the observation, interview and documentation.The results of this study revealed that: 1) Kaweruh Jawa Dipa quite scattered in the district Tulungagung, and the central leadership of branches located in the hamlet Miren, Ngranti village, district Boyolangu, Tulungagung. The existence of this group can be seen from some of the teachings and the role played,especially in the realm of the role of socio-cultural and socio-educational. 2) Teachings of Kaweruh Jawa Dipa group that teaches the philosophy of divinity and philosophy of Pancasila.Kata kunci: Penghayat Kepercayaan, Kaweruh Jawa Dipa, Filsafat Pancasila.